Association Between Smoking and Periodontitis in the National Health and Nutrition Examination Survey (NHANES) 2012. - ALHarthi, Shatha. (2017)
Abstract: Aim & Hypothesis: The experimental aims of the study were to use the National Health and Nutrition Examination Survey (NHANES) dataset to test and confirm the following hypotheses: 1) Characterize the periodontal condition among never smokers, former smokers and current smokers, 2) Analyze the association of time since quitting smoking and the periodontal condition among former smokers as a function of smoking history, 3) Analyze the association of duration of smoking and the periodontal condition among current smokers as a function of smoking history. Materials & Methods: This study analyzed data collected in the NHANES 2012 survey and included respondents for whom a periodontal exam and smoking status were obtained. Aim 1 was a descriptive analysis were used to characterize the sample. For Aim 2, unconditional logistic regression was conducted with time since quitting as the exposure and presence of periodontitis as the outcome, and included adjustment for confounders. Aim 3 analyses also used unconditional logistic regression, but included only current smokers, with duration of smoking habit as the exposure and periodontitis status as the outcome, adjusted for confounders. Results: Smoking status was statistically significantly associated with periodontal status (chi-square p < 0.0001). Among former smokers, after adjusting for confounders, each additional year since quitting smoking was associated with a statistically significant reduction in the odds ratio (OR) for periodontitis by 2.5%. Among current smokers, duration of smoking was not statistically significantly associated with periodontal status. Conclusions: Rates of periodontitis were highest in current smokers, lower in former smokers, and lowest in never smokers. Among former smokers, longer time since quitting was associated with lower likelihood of periodontitis. Among current smokers, the duration of smoking was not associated with likelihood of periodontitis. These findings support the notion that that dental practitioners have a public health mandate to help their periodontal patients quit smoking. Future research should determine the best strategies for facilitating smoking cessation in dental patients.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Periodontology.; Advisor: Bjorn Steffensen.; Committee: Jennifer Bassett Midle, Robert Gyurko, and Rory O'Neill.; Keywords: Dentistry, and Public health.